Dampak Interaksi Manusia Dengan Robot Dalam Novel Life Hack Karya June Perry - Delfa Mahsa Hustaqoria; Keisya Ayu Maharani; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The purpose of this study is to determine the influence of human interaction with robots in a novel. The genre of literary works used is a novel by June Perry entitled Life Hack. The problem raised in this novel is how the influence of human interaction with robots. The presence of a girl who suddenly takes away everything Ellie has, friends, crushes, home, even Ellie's only father. What if humanoid robots take over human life completely? Will it bring progress or destruction? The data in this study are written data in the form of story text related to humanoid robots contained in the novel Life Hack by June Perry. The method used is descriptive qualitative and hermeneutic method using reading and note-taking technique. This research was conducted by analyzing the data contained in the novel Life Hack. The results found are in the form of positive and negative impacts of human interaction with robots in the novel Life Hack.